Self perception and facial emotion perception of others in anorexia nervosa - Phillipou, Andrea; Abel, Larry A.; Castle, David J.; Hughes, Matthew E.; Gurvich, Caroline; Nibbs, Richard G.; Rossell, Susan L. (Frontiers in Psychology, 2015)
Background: Whether individuals with anorexia nervosa (AN) are able to accurately perceive emotions from faces of others is unclear. Furthermore, whether individuals with AN process images of their own face differently to healthy individuals has thus far not been investigated. Therefore, the aim of this study was to investigate facial affect processing and the processing of one’s own face through measures of emotion identification, functional magnetic resonance imaging (fMRI) and eyetracking. Methods: 24 females with AN and 25 matched healthy control participants were presented with an implicit emotion processing task during fMRI and eyetracking, followed by an explicit emotion identification task. Results: The AN group were found to ‘hyperscan’ stimuli and avoided visually attending to salient features of their own face images. Results of the fMRI revealed increased activity to own face stimuli in AN in the right inferior and middle temporal gyri, and right lingual gyrus. AN participants were not found to display emotion identification deficits to the standard emotional face stimuli. Discussion: The findings are discussed in terms of increased anxiety to disorder-relevant stimuli in AN. Potential clinical implications are discussed in relation to the use of eyetracking techniques to improve the perception of self in AN.